Patient-identified burden and unmet needs in patients with cluster headache: An evidence-based qualitative literature review - Emily Freeman (Cephalalgia Reports, 2022)
Objectives: To qualitatively identify evidence-based literature related to the daily burden and unmet treatment and psychosocial needs of patients with cluster headache (CH). Methods: A literature search was conducted through October 20, 2020 across MEDLINE, EMBASE, CINAHL, and PsychInfo databases exploring quality of life (QoL) and disease burden in adults with CH. The search was restricted to full-text reports in peer-reviewed journals. Methodologic quality was assessed using the Critical Skills Appraisal Program. Results: From 11 identified publications, QoL was reduced in persons living with CH, with significant psychological, social, and socio-economic burdens, and work-related disability. The CH disease trajectory is complex, with patients experiencing the impact of their disease across multiple domains beyond the biological manifestation of the disease including stigma, employment limitations, and suicidal ideation, and with a lack of effective treatment from the patient perspective. Discussion: These findings strengthen comprehension of the CH patient experience, enabling a deeper understanding of the patients’ perspective and experience of their disease andunmet needs, providing a basis for future research into this debilitating condition. Minor limitations of this study include data extraction and study selection biases.